X-Ray Diffraction and Vibrational Spectroscopic Characteristics of Hydroxylclinohumite from Ruby-Bearing Marbles (Luc Yen District, Vietnam). (29th January 2014) - Hurai, V.; Wierzbicka-Wieczorek, M.; Pentrák, M.; Huraiová, M.; Thomas, R.; Swierczewska, A.; Luptáková, J.
Abstract : A honey-yellow hydroxylclinohumite from ruby-bearing marbles of the Luc Yen district in northern Vietnam was characterized by electron microprobe (EPMA), single-crystal X-ray diffraction (XRD), micro-Raman, and Fourier-transform infrared (FTIR) spectroscopy. The studied crystals correspond to nearly ideal clinohumite with the structural formula 4[Mg2 SiO4 ]· [(Mg, Fe, Ti)(OH, F)2 ] and roughly equal F and OH proportions. Crystal structure analysis showed Ti substitution for Mg only at the Mg3 site. A Fourier-difference map revealed one hydrogen site associated with ninth oxygen atom. The calculated O–H bond distance was shorter than that in other natural clinohumites. FTIR revealed bands corresponding to combination of OH-stretching with Mg–OH and/or Fe–OH bending modes, combinations of OH − and Fe–OH vibrations, combination of fundamental bands of the Si–OH bonding, combination of OH − and Si–OH vibrations, and first (2ν OH ) and the second (3ν OH ) overtones of the OH-stretching vibration mode. Two groups of OH-stretching vibration and FTIR absorption bands at 3390–3420 cm −1 and 3560–3580 cm −1 show reversible temperature-dependent shift. The low-frequency bands absent in pure synthetic hydroxylclinohumites are assigned to OH-planar defects caused by Ti-for-Mg substitution.